Personalized treatment of extensive stage small cell lung cancer: A case report and literature review - Wang, Huaiyu; Wang, Xuning; Jiang, Suxin; Zhu, Jingna; Liu, Jie; Zhou, Chuanhong; Zhu, Yanjun; Han, Yong (Frontiers in Oncology, 2022)
A 50-year-old female patient presented with post-exercise dyspnea in September 2016, and was subsequently diagnosed with SCLC with multiple brain and spinal metastases. The first-line treatment was Etoposide combined with Cisplatin, and synchronously performed radiotherapy for the brain and spinal cord metastasis. She was treated with anlotinib after disease progression in December 2018 and continued clinical benefit for nearly 25 months. Unexpectedly, the patient can still benefit from further combination treatment with Durvalumab after another disease progression in February 2021. Thus, it may be a potential option to use anlotinib in combination with immunotherapy after the anlotinib resistance in SCLC, but more clinical data are still needed to confirm it. Moreover, ctDNA dynamic monitoring was performed and reflected the outcome in the process of treatment.